Nasal Septum Deviation as the Consequence of BMP-Controlled Changes to Cartilage Properties - Baddam, Pranidhi; Young, Daniel; Dunsmore, Garett; Nie, Chunpeng; Eaton, Farah; Elahi, Shokrollah; Jovel, Juan; Adesida, Adetola B.; Dufour, Antoine; Graf, Daniel (Frontiers in Cell and Developmental Biology, 2021)
The nasal septum cartilage is a specialized hyaline cartilage important for normal midfacial growth. Abnormal midfacial growth is associated with midfacial hypoplasia and nasal septum deviation (NSD). However, the underlying genetics and associated functional consequences of these two anomalies are poorly understood. We have previously shown that loss of Bone Morphogenetic Protein 7 (BMP7) from neural crest (BMP7ncko) leads to midfacial hypoplasia and subsequent septum deviation. In this study we elucidate the cellular and molecular abnormalities underlying NSD using comparative gene expression, quantitative proteomics, and immunofluorescence analysis. We show that reduced cartilage growth and septum deviation are associated with acquisition of elastic cartilage markers and share similarities with osteoarthritis (OA) of the knee. The genetic reduction of BMP2 in BMP7ncko mice was sufficient to rescue NSD and suppress elastic cartilage markers. To our knowledge this investigation provides the first genetic example of an in vivo cartilage fate switch showing that this is controlled by the relative balance of BMP2 and BMP7. Cellular and molecular changes similar between NSD and knee OA suggest a related etiology underlying these cartilage abnormalities.